PEMBINAAN IMPLEMENTASI 4 METODE PENGHITUNGAN SERTA BAGIAN-BAGIAN AHLI WARIS BAGI SANTRI KELAS 6 MMU B-73 LOMBOK KULON - Ifan Afandy; Muhammad Husni (Abdimas Aswaja: Jurnal Pengabdian Masyarakat, 2026)
The science of Mawaris or Faraidh is a science whose interest is decreasing every time. We have felt this together today, in fact this reality was conveyed specifically by the Prophet sallallaahu 'Alaihi Wasallam 1400 years ago. In the hadith narrated by Imam Ibn Majah number 2719, the Prophet said to  Abu Hurairah which means: "O Abu Hurairah, learn the science of faraidh and teach it, because in fact it is half of knowledge. And that knowledge will be forgotten and it is the first knowledge to be revoked from my people." This includes the 6th grade students of MMU (Madrasah Miftahul Ulum) B-73 Darul Maghfur Islamic Boarding School who are starting to feel bored and tired of understanding this knowledge. It was proven that their 1st dan 2nd examanation (IMDA) scores had dropped and were in the red.  The purpose of this research is to provide education and specific direction to the 6th grade students of MMU (Madrasah Miftahul Ulum) B-73 Pesantren Darul Maghfur so that they truly understand the 4 calculation methods in the science of Faraidh and the parts of the heirs in an easier, more practical, and interesting way, so that they can master this scientific field well and get written and practical exam scores that meet the graduation requirements in IMNI (Imtihan Niha'i) organized by the Sidogiri Islamic Boarding School which is the parent of the Madrasah. The method used was descriptive qualitative through interviews, observation, and documentation. After the mentoring, the students became more active and creative in creating problem formulation tables, memorizing the number of heirs and their components, creating problem outlines, and presenting inheritance problems and their solutions to other students.